Fabrikasi Material Komposit Anti Peluru Carbon Fiber-Epoxy Resin Berpenguat Nanokristal Selulosa Berbasis Limbah Kertas - Roehafi, Firza; Herman Aldila (Jurnal Riset Fisika Indonesia, 2025)
Waste paper contains up to 64.84% cellulose, making it a potential raw material for the synthesis of nanocrystalline cellulose (NCC) via sulfuric acid (H₂SO₄) hydrolysis. The use of 1M H₂SO₄ produced NCC with favorable characteristics, including a cellulose purity of 80.79%, a crystallinity index of 88.73%, and a crystal size of 3.18 nm. Subsequently, bulletproof composites were fabricated using carbon fiber–epoxy resin reinforced with nanocrystalline cellulose. The independent variable in this study was the ratio between nanocrystalline cellulose powder and epoxy resin. The fabricated bulletproof composites measured 200 × 200 mm in area and had a thickness of 20 mm. The results showed that composites containing 0% and 10% NCC (designated as KAP-01 and KAP-02) were capable of withstanding the impact of 9×19 mm handgun bullets, meeting the requirements of NIJ Standard-0101.04 Level IIIA. However, the bulletproof composites in this study were not able to resist penetration from 5.56×45 mm rifle rounds.